Pengujian Teori Trade-Of Dan Pecking Order Dengan Satu Model Dinamis Pada Perusahaan Publik Di Indonesia - Adler Haymans Manurung, Darminto., (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2008)
This article explores determinant of capital structure in Indonesia.Empirical study using Regression in model is done by includingvariable suggested by Trade of Theory, Pecking Order Theory, andcombination of those theories. The result shows that determinantfactors in the Trade of Theory have more ability to explain the capitalstructure than deficit cash flow factor in pecking order theory. Othervariables that are also significant are firm size and collateral capacity.Its is possible that rejection of Pecking Order Theory is due to markettiming argument in long term financing.Keywords: leverage, pecking order theory, trade-off theory, capital structure, size and tangible fxed asset.